2019
DOI: 10.1002/ppsc.201900100
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin‐Carbon‐Layer‐Protected PtCu Nanoparticles Encapsulated in Carbon Capsules: A Structure Engineering of the Anode Electrocatalyst for Direct Formic Acid Fuel Cells

Abstract: Structure engineering is an effective strategy to enhance the performance of electrocatalysts for the formic acid oxidation reaction. However, it remains a challenge to prepare a highly active electrocatalyst based on a distinct understanding of its structure‐dependent performance. The design and synthesis of ultrathin‐carbon‐layer‐protected PtCu nanoparticles (NPs) encapsulated in a N‐doped carbon capsule (PtCu@NCC) is reported. This system is fabricated by using Zn‐based metal–organic frameworks as the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…In addition, a high mass activity of 1.37 mA • mg Pt À 1 has been reported. [115] Yanping et al demonstrated a novel process by fabricating PtCU nanowire (NW) gas diffusion electrodes (GDE) to be used as a direct anode for DFAFC. PtCu alloy NWs are directly grown on a gas diffusion layer by formic acid reduction and can be directly used as GDEs.…”
Section: Coppermentioning
confidence: 99%
“…In addition, a high mass activity of 1.37 mA • mg Pt À 1 has been reported. [115] Yanping et al demonstrated a novel process by fabricating PtCU nanowire (NW) gas diffusion electrodes (GDE) to be used as a direct anode for DFAFC. PtCu alloy NWs are directly grown on a gas diffusion layer by formic acid reduction and can be directly used as GDEs.…”
Section: Coppermentioning
confidence: 99%
“…(a) TEM images of Pd 1 Ir 2 /MWCNT and Pd 2 Ir 1 /MWCNT hybrids (Reprinted with permission (through Copyright Clearance Central) from reference (Hao et al, 2016) Copyright © 2015, Elsevier); (b) TEM and EDX maps of PdCu@Pd tetrahedra (Reprinted with permission (through Copyright Clearance Central) from reference (Y. Chen, Yang, et al, 2018) Copyright © 2018, The Royal Society of Chemistry); (c) SEM and STEM image of PtCu@NCC electrocatalyst (Reprinted with permission (through Copyright Clearance Central) from reference (M. Xu et al, 2019) Copyright © 2019, WILEY‐VCH Verlag GmbH & co. KGaA, Weinheim); (d) TEM and FESEM image of PdPb flower‐like intermetallic nanocrystals (Reprinted with permission (through Copyright Clearance Central) from reference (Jana et al, 2016) Copyright © 2015, Elsevier); (e) SEM and TEM images, corresponding SAED pattern and EDX mapping of Pd‐Sn‐INNs (Reprinted with permission (through Copyright Clearance Central) from reference (D. Sun, Si, et al, 2015) Copyright © 2015, Elsevier); (f) TEM images and their corresponding EDX images as well as single cell performance data of the carbon supported Pd and PdFe electrocatalysts (Reprinted with permission (through Copyright Clearance Central) from reference (Kang et al, 2020) Copyright © 2020, American Chemical Society); (g) The TEM images of (A) Pd 1 Ru 9 ( d = 5.90 ± 0.51), (B) Pd 3 Ru 7 (14.6 ± 1.6), (C) Pd 7 Ru 3 ( d = 8.5 ± 0.9), and (D) Pd 9 Ru 1 ( d = 10.7 ± 1.2) nanoparticles (Reprinted with permission (through Copyright Clearance Central) from reference (Miao et al, 2017) Copyright © 2017, Elsevier)…”
Section: Anode Electrocatalystsmentioning
confidence: 99%
“…The NC-encapsulated PtCu thus formed (Figure 5c) had a unique structure and protective coating, which led to high performance and stability in both half-cell and full-cell studies, with a maximum power density (MPD) of 121 mW cm À2 . It also exhibited a 30% higher retention in peak power density than Pt/C after a 40 h durability test (M. Xu et al, 2019).…”
Section: Alloying Of Noble Metalsmentioning
confidence: 99%
“…Research studies have demonstrated a big disparity for highly active shape-controlled catalysts between their intrinsic catalytic activities measured in liquid electrolytes and their power performance within practical catalyst electrodes in fuel cell devices . Most of these catalysts showed limited improvement or even worse power performance compared to commercial catalysts in the single fuel cell test, compared with their excellent catalytic activities revealed in the half cell electrochemical measurement, which is mainly caused by the mass transport resistance under the complex environment conditions within the practical electrodes during the fuel cell operation. ,, Therefore, to fabricate practical electrodes based on these shape-controlled catalysts, a new electrode approach is urgently required to improve mass transport resistance thus achieving high power performance. Here, we demonstrate a facile method to fabricate gas diffusion electrodes (GDEs) by directly growing PtCu nanowire (NW) arrays on the carbon paper gas diffusion layer (GDL) surface at room temperature without using any template or surfactant.…”
Section: Introductionmentioning
confidence: 99%